Dissecting macrophage heterogeneity and kaempferol in lung adenocarcinoma: a single-cell transcriptomic approach and network pharmacology - Laiyi Wan; Wentao Hao; Leilei Li; Lin Wang; Yanzheng Song (Discover Oncology)
Abstract Background Lung adenocarcinoma (LUAD) is a leading form of non-small cell lung cancer characterized by a complex tumor microenvironment (TME) that influences disease progression and therapeutic response. Tumor-associated macrophages (TAMs) within the TME promote tumorigenesis and evasion of immune surveillance, though their heterogeneity poses challenges in understanding their roles and therapeutic targeting. Additionally, traditional Chinese medicine (TCM) offers potential anti-cancer agents that could modulate the immune landscape. Methods We conducted single-cell RNA sequencing (scRNA-seq) on LUAD samples, performing an in-depth analysis of macrophage populations and their expression signatures. Network pharmacology was used to identify TCM components with potential TAM-modulatory effects, focusing on Astragalus membranaceus. Pseudotime trajectory analysis, immunofluorescence staining, and in vitro assays examined the functional roles of TAMs and the effects of selected compounds on macrophage polarization. Results Our scRNA-seq analysis identified notable heterogeneity among macrophages, revealing predominant M2-like phenotypes within TAMs. Network pharmacology highlighted active TCM ingredients, including quercetin, isorhamnetin, and kaempferol, targeting genes related to macrophage function. Survival analysis implicated AHSA1, CYP1B1, SPP1, and STAT1 as prognostically significant factors. Further experiments demonstrated kaempferol’s efficacy in inhibiting M2 polarization, underlining a selective influence on TAM functionality. Conclusions This study delineates the diverse macrophage landscape in LUAD and suggests a pivotal role for STAT1 in TAM-mediated immunosuppression. Kaempferol, identified from TCM, emerges as an influential agent capable of altering TAM polarization, potentially enhancing anti-tumoral immunity. These findings underscore the translational potential of integrating TCM-derived compounds into immunotherapeutic strategies for LUAD.